MENINGKATKAN KEMAMPUAN GURU SMP DALAM MELAKSANAKAN KBM MODEL TGT (TEAMS GAMES TOURNAMENT) MELALUI SUPERVISI AKADEMIK KEPALA SEKOLAH - Musimin Musimin; Suntoro Suntoro (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
This study aims to improve the ability of teachers in carrying out teaching and learning activities through the Team Games Tournament (TGT) learning model through the academic supervision of the principal of SMP Negeri 1 Batang Kuis. This research was designed through school action research with a four-stage model, namely planning, action, observation, and reflection which was carried out at SMP Negeri 1 Batang Kuis. The subjects of this research were 15 teachers of SMP Negeri 1 Batang Kuis. This study uses 2 cycles. Data collection techniques using observation. The results obtained are that the cooperative learning model type Team Games Tournament (TGT) can improve the ability of teachers in implementing KBM. In the first cycle the teacher's ability to apply the TGT model with an average of 74.6 in the medium category. In the second cycle there was an increase with an average of 87.5 with a high category. In the second cycle, the teacher was able to understand the application of the TGT type cooperative learning model so that student activity and learning outcomes were achieved to the maximum